Dietary arginine requirement of juvenile swimming crab, Portunus trituberculatus. (21st November 2015) - Jin, M.; Zhou, Q.C.; Wang, M.Q.; Huo, Y.W.; Huang, W.W.; Mai, K.S.
Abstract: An 8‐week feeding trial was conducted to determine the optimal dietary arginine requirement for juvenile swimming crab Portunus trituberculatus . Six isonitrogenous and isolipidic experimental diets were formulated to contain graded arginine levels which ranged from 15.9 to 33.0 g kg −1 . Each diet was randomly assigned to triplicate groups of 60 juvenile swimming crabs (4.72 ± 0.12 g). The results indicated that dietary arginine had significant effects on weight gain (WG), specific growth rate (SGR), protein productive value, feed efficiency and protein efficiency ratio. Weight gain and SGR significantly increased with the dietary arginine increasing from 15.9 to 27.4 g kg −1, while with the further increasing from 27.4 to 33.0 g kg −1, WG and SGR did not increase significantly. Maximum arginine, proline and total essential amino acid contents in muscle were observed in 27.4 g kg −1 group diet. The swimming crab fed the diet with lower dietary arginine level showed higher AST and lower ALT in the serum. Crab fed with the lower dietary arginine level had significantly lower ALT in the serum than the other groups. Haemolymph indexes were significantly affected by the dietary arginine level except for the cholesterol concentration, and the highest values were all found in 27.4 g kg −1 group diet. The two slope broken‐line model using SGR showed that the optimal dietary arginine requirement was 27.7 g kg −1 of the dry matter (56.0 g kg −1 dietary protein) for juvenile swimming crab.